2020
DOI: 10.1128/jvi.00148-20
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting BMS-378806 Analogues Stabilize the State-1 Conformation of the Human Immunodeficiency Virus Type 1 Envelope Glycoproteins

Abstract: During human immunodeficiency virus type 1 (HIV-1) entry into cells, the viral envelope glycoprotein (Env) trimer [(gp120/gp41)3] binds the receptors CD4 and CCR5 and fuses the viral and cell membranes. CD4 binding changes Env from a pretriggered (state-1) conformation to more open downstream conformations. BMS-378806 (here called BMS-806) blocks CD4-induced conformational changes in Env important for entry and is hypothesized to stabilize a state-1-like Env conformation, a key vaccine target. Here, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 69 publications
6
63
0
Order By: Relevance
“…In contrast to the other classes of ARVs, the Env mutants we identified in NL4-3 and K3016 are sensitive to two types of Ent-Is: a fusion inhibitor (T-20) and a compound that blocks CD4-induced conformational changes in Env (BMS-378806) (19,(65)(66)(67). Previous studies have shown that Ent-Is targeting CD4 or a coreceptor are effective in blocking cell-cell transmission (34,60,93).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast to the other classes of ARVs, the Env mutants we identified in NL4-3 and K3016 are sensitive to two types of Ent-Is: a fusion inhibitor (T-20) and a compound that blocks CD4-induced conformational changes in Env (BMS-378806) (19,(65)(66)(67). Previous studies have shown that Ent-Is targeting CD4 or a coreceptor are effective in blocking cell-cell transmission (34,60,93).…”
Section: Discussionmentioning
confidence: 83%
“…These findings raise the possibility that Env mutations selected in the presence of ARVs might alter the viral sensitivity to Env-targeted inhibitors. To examine this question, we measured replication kinetics in the presence of the fusion inhibitor T-20 and BMS-378806, which blocks CD4-induced conformational changes in Env (19,(65)(66)(67). Interestingly, these Ent-Is efficiently suppressed replication of both WT NL4-3 and Env-A539V with no statistically significant differences in antiviral IC 50 s in a multicycle spreading infection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antibody or ligand binding and smFRET analyses indicate that the Env precursor can sample multiple conformations that resemble States 1, 2 and 3 of the mature viral Env spike (73)(74)(75)(76)(77)(78)(79)(80)(81). The conformational plasticity of the Env precursor contrasts with the behavior of the mature Env, which in the absence of ligands largely resides in State 1 (42,81).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 29, 2021. ; https://doi.org/10.1101/2021.03.28.437443 doi: bioRxiv preprint BMS-806 can enrich State 1 in the uncleaved membrane-anchored Env (79,81) and BS3 crosslinking could hypothetically help to stabilize this conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation